Challenges in reducing grand multiparity rates in Ethiopia: an analysis of 2019 EDHS data using a multilevel model approach - Diriba Dibaba; Tesfaye Getachow Charkos (Contraception and Reproductive Medicine)
Abstract Background One of the Sustainable Development Goals (2030) focuses on reducing the total fertility rate. Reducing grand multiparity in Ethiopia remains a challenge. Understanding the underlying factors that contribute to this issue is crucial for explaining why grand multiparity remains prevalent despite various health interventions and socio-economic progress. Methods A community-based cross-sectional study was conducted using data from the Ethiopian Demographic and Health Survey 2019. Multilevel multivariable logistic regression analysis was employed to model the hierarchical data. The final findings were presented as adjusted odds ratios (AOR) with 95% confidence intervals (CI). A p-value < 0.05 was considered statistically significant. Result The trend analysis of grand multiparity in Ethiopia over 19 years shows no significant change (linear trend = 1.23, p = 0.27). The prevalence slightly decreased from 72% in the 2000 EDHS to 66.3% (95% CI: 65.7 − 66.96%) in the 2019 mini EDHS. Additionally, the highest prevalence of grand multiparity was observed among illiterate women (79.7%), those from poor households (54.8%), non-family planning users (77.5%), and residents of the Oromia (15.8%) and SNNPR (15.4%) regional states. Significant individual-level factors associated with grand multiparity include wealth index, marital status, maternal education, non-use of family planning, use of short-acting family planning, age at first birth < 18 years, and short birth intervals. At the community level, rural residency was significantly associated with grand multiparity. Conclusion This study emphasizes the need for targeted interventions to address the socio-economic and reproductive factors driving grand multiparity, especially in rural areas and among disadvantaged populations. To improve maternal and child health outcomes, we recommend that the government focus on lowering fertility rates through need-based family planning services and promoting the well-being of women of reproductive age.